The edge of objectivity : - Gillispie, Charles Coulston (Princeton University Press, 1960)
From Galileo's analysis of motion to the theories of evolution and relativity, Charles Gillispie takes us on a masterly tour of the world of scientific ideas. The history of modern science is portrayed here as the development of objectivity through the study of nature.